2011
DOI: 10.1016/j.joca.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mechanical stress-induced MMP-13 and ADAMTS-5 expression by RUNX-2 transcriptional factor in SW1353 chondrocyte-like cells

Abstract: RUNX-2 might have a role as a key downstream mediator of p38's ability to regulate mechanical stress-induced MMP-13 and ADAMTS-5 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 49 publications
7
118
0
Order By: Relevance
“…The stress-induced MAPK pathways, including the ERK, c-Jun N-terminal kinase (JNK) and p38 MAPK cascades, coordinate the induction and activation of gene expression through transcription factors such as activator protein 1 (cFos/cJun), ETS, C/EBPβ, and Runx2 [Goldring and Sandell, 2007;Long and Loeser, 2010;Tetsunaga et al 2011;Tsuchimochi et al 2010]. Induction of both ADAMTS4 and 5 requires Runx2 [Tetsunaga et al 2011], and NFκB and HIF2α [Yang et al 2010] mediate ADAMTS4 upregulation, whereas MMP-13 induction requires all three transcription factors. Recent studies indicate that epigenetic mechanisms also play a role through modulation of the DNA methylation status on promoters driving expression of, for example, IL1B and MMP13 genes [Hashimoto et al 2009] or through dysregulation of the microRNAs that are important for maintenance of homeostasis [Dudek et al 2010;Miyaki et al 2010].…”
Section: Inflammation and Mechanical Stress In Osteoarthritismentioning
confidence: 99%
“…The stress-induced MAPK pathways, including the ERK, c-Jun N-terminal kinase (JNK) and p38 MAPK cascades, coordinate the induction and activation of gene expression through transcription factors such as activator protein 1 (cFos/cJun), ETS, C/EBPβ, and Runx2 [Goldring and Sandell, 2007;Long and Loeser, 2010;Tetsunaga et al 2011;Tsuchimochi et al 2010]. Induction of both ADAMTS4 and 5 requires Runx2 [Tetsunaga et al 2011], and NFκB and HIF2α [Yang et al 2010] mediate ADAMTS4 upregulation, whereas MMP-13 induction requires all three transcription factors. Recent studies indicate that epigenetic mechanisms also play a role through modulation of the DNA methylation status on promoters driving expression of, for example, IL1B and MMP13 genes [Hashimoto et al 2009] or through dysregulation of the microRNAs that are important for maintenance of homeostasis [Dudek et al 2010;Miyaki et al 2010].…”
Section: Inflammation and Mechanical Stress In Osteoarthritismentioning
confidence: 99%
“…Using this apparatus, the entire silicon membrane can be stretched uniformly [23,24]. In the current study, a CTS (0.5 Hz, 10 % elongation) was applied for 30 min as described in our previous study [22,25]. Cells incubated without mechanical stress were used as control.…”
Section: Stretching Experimentsmentioning
confidence: 99%
“…In addition, it has been suggested that inflammatory cytokines such as IL-1b also play an important role in regulating the expression of ADAMTSs or MMPs [22]. In the current study, we used human chondrocytes to examine whether HA affects the mechanical stress-induced gene expression of ADAMTS-4, ADAMTS-5, and MMP-13 in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Proteoglycan and collagen degradation are principally carried out by members of the matrix metalloproteinase (MMP) family, such as MMP3, MMP7, and MMP13, which play important roles in degrading cartilage collagens [7][8][9]. However, previous biochemical studies have demonstrated that members of the a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) family such as ADAMTS-1, -4, -5, -8, -9, and -15 possess aggrecanase activity and can induce the degradation of cartilage proteoglycan-aggrecan in OA [10][11][12][13][14]. Knockdown of ADAMTS-4/5 exerted protective effects against proteoglycan degradation and attenuated the severity of murine OA [15], and the degradation of aggrecan was decreased when ADAMTS-4/5 small interfering RNA was used in human cartilage stimulated by IL-1β [16].…”
Section: Introductionmentioning
confidence: 99%